Answer:
<h2>2x^3+3x^2</h2>
Step-by-step explanation:
<h3>x^2(2x+3)</h3><h3 /><h3>=(x^2)(2x+3)</h3><h3 /><h3>=(x^2)(2x)+(x^2)(3)</h3><h3 /><h3>=2x^3+3x^2</h3>
Answer:
w = -20
Step-by-step explanation:
-
+ 9 = 13
Shift the (+9) to the other side of the equation. (+9) will turn into (-9).
-
= 13 - 9
= 4
Shift the (÷5) to the other side of the equation. (÷5) will turn into (×5).
-w = 4 × 5
= 20
Multiply both sides of the equation by (-1) so that -w will turn into w.
w = (-1) × 20
w = -20
Answer:
154 Minutes
Step-by-step explanation:
So first we know that:
28 divided by 14 is:
2
Next Multiply 77 by 2:
154 Minutes
Hence, the correct answer is 154 Minutes